Bay-annulated indigo derivatives based on a core of spiro[fluorene-9, 9′-xanthene]: Synthesis, photophysical, and electrochemical properties. (January 2019) - Ren, Bao-Yi; Xu, Qin; Kolaczkowski, Matthew; Sun, Chang-Liang; Ou, Chang-Jin; Sun, Ya-Guang; Xie, Ling-Hai; Huang, Wei
Abstract: Two positional isomers based on a spiro[fluorene-9, 9′-xanthene] (SFX) core were synthesized by selectively appending bay-annulated indigo (BAI) units to the fluorene moiety or the xanthene moiety of SFX, respectively. Investigation of photophysical and electrochemical properties revealed that the two compounds were endowed with broad absorption, low LUMO level, and weak aggregation characteristics. The rational combination of planar BAI units with a three-dimensional SFX core makes them attractive n -type candidates for eco-friendly and sustainable organoelectronic devices. Graphical abstract: Image 1